English as second language learners' practices and experiences with written feedback - Kloss, Steffanie; Quintanilla, Angie (Frontiers in Education, 2024)
Feedback remains a controversial topic for several reasons, the most relevant being the effectiveness and students' appraisal of the practice. This article explores second language learners' perceptions of feedback as a teaching and learning strategy. In second language teaching, it is necessary to know learners’ previous knowledge and experiences regarding how they receive feedback, since this practice has an impact on the improvement of writing. To this end, in this research, an online questionnaire was distributed to 202 participants taking an English course to ask them about: types of feedback received, preferences regarding feedback, effectiveness of feedback and experiences with feedback. Analysis of their responses, quantitative and qualitative, shows that participants have preferences about how they expect feedback to be given, although these are not consistent with what theory suggests as effective. In addition, participants argue that their experience with feedback is related to a rather normative correction in which teachers focus on attending to microstructural aspects; therefore, students' view of textual quality is linked to normative processes. These aspects are important to address in the development of writing classes for second-language learners.